(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This text makes a brief analysis of the dramaturgical process from the epic to the dramatic literary text and highlights some considerations about theoretical production based on theatrical historical aspects that address the theme and highlight some terminologies about the movement from one genre to the other. The theoretical research for the preparation of this article began in the master’s degree with the dissertation entitled, The crossing of the narrative to the dramatic in the educational context, in the Postgraduate Program in Performing Arts, PPGAC, UFBA, in 2011, made me reflect on how dramaturgy appeared in my artistic-pedagogical activities.